The gap gene giant of Rhodnius prolixus is maternally expressed and required for proper head and abdomen formation - Lavore, Andrés E. (2012)
The segmentation process in insects depends on a hierarchical cascade of gene activity. The first effectors downstream of the maternal activation are the gap genes, which divide the embryo in broad fields. We discovered a sequence corresponding to the leucine-zipper domain of the orthologue of the gene giant (Rp- gt) in traces from the genome of Rhodnius prolixus, a hemipteran with intermediate germ-band development. We cloned the Rp- gt gene from a normalized cDNA library and characterized its expression and function. Bioinformatic analysis of 12.5. kbp of genomic sequence containing the Rp- gt transcriptional unit shows a cluster of bona fide regulatory binding sites, which is similar in location and structure to the predicted posterior expression domain of the Drosophila orthologue. Rp-gt is expressed in ovaries and maternally supplied in the early embryo. The maternal contribution forms a gradient of scattered patches of mRNA in the preblastoderm embryo. Zygotic Rp-gt is expressed in two domains that after germ band extension are restricted to the head and the posterior growth zone. Parental RNAi shows that Rp-gt is required for proper head and abdomen formation. The head lacks mandibulary and maxillary appendages and shows reduced clypeus-labrum, while the abdomen lacks anterior segments. We conclude that Rp-gt is a gap gene on the head and abdomen and, in addition, has a function in patterning the anterior head capsule suggesting that the function of gt in hemipterans is more similar to dipterans than expected.